Problemas de expresión oral en estudiantes de bachillerato de la Unidad Educativa “Pedro Vicente Maldonado”, Riobamba, período lectivo 2022. - Caiza Shagñay, Luis David (2023)
This investigative work sought to respond to a problem that occurs in educational units; Oral expression problems in students, as is known in the area of Language and Literature, this skill stands out for its importance in order to carry out an effective communication process. The main objective was to analyze the problems of oral expression, in such a way that each one of the difficulties is identified to propose an intervention plan that serves as a treatment. Taking into account how oral expression problems influence students. The methodology responded to a qualitative approach, with a descriptive level, because the place is field and according to its modality it is non-experimental. The population is the first-year high school students of the Unidad Educativa Pedro Vicente Maldonado, with its corresponding sample of the first-year parallel “B” high school students. The techniques that were used for the collection of information were a survey and observation with its pertinent instruments: the questionnaire and the evaluation rubric. After the results obtained, it demonstrates the existence of oral expression problems and speech disorders in students. It was concluded with the design of intervention plans, which are recommended to the teacher to practice with the student to improve oral expression.